Catheter Ablation of Asymptomatic Longstanding Persistent Atrial Fibrillation: Impact on Quality of Life, Exercise Performance, Arrhythmia Perception, and Arrhythmia‐Free Survival. (7th July 2014) - MOHANTY, SANGHAMITRA; SANTANGELI, PASQUALE; MOHANTY, PRASANT; BIASE, LUIGI DI; HOLCOMB, SHAWNA; TRIVEDI, CHINTAN; BAI, RONG; BURKHARDT, DAVID; HONGO, RICHARD; HAO, STEVEN; BEHEIRY, SALWA; SANTORO, FRANCESCO; et al.
Ablation Outcome in Silent Longstanding Persistent AF Background Impact of catheter ablation on exercise performance, quality of life (QoL) and symptom perception in asymptomatic longstanding persistent AF (LSP‐AF) patients has not been reported yet. Methods and Results Sixty‐one consecutive patients (mean age 62 ±13 years, 71% males) with asymptomatic LSP‐AF undergoing first catheter ablation were enrolled. Extended pulmonary vein antrum isolation plus ablation of complex fractionated atrial electrograms and nonpulmonary vein triggers was performed in all. QoL survey was taken at baseline and 12‐months postablation, using Short Form‐36 (SF‐36). Information on arrhythmia perception was obtained using a standard questionnaire and corroborating symptoms with documented evidence of arrhythmia. Exercise tests were performed on 38 patients at baseline and 5 months after procedure. Recurrence was assessed using event recorder, cardiology evaluation, electrocardiogram, and 7‐day holter monitoring. After 20 ± 5 months follow‐up, 36 (57%) patients remained recurrence‐free off‐AAD. Of the 25 patients experiencing recurrence, 21 (84%) were symptomatic. Compared to baseline, follow‐up SF‐36 scores improved significantly in many measures. For patients with successful ablation, physical component summary (PCS) and mental component summary (MCS) demonstrated substantial improvement (MCS: 64.2 ± 22.3 to 70.1 ± 18.6 [P = 0.041]; PCS: 62.6 ± 18.4 to 70.0 ± 14.4 [P = 0.032]). Postablation exercise study in recurrence‐free patients showed significant reduction in resting and peak heart rate (75 ± 11 vs. 90 ± 17 and 132 ± 20 vs. 154.5 ± 36, respectively, P < 0.001), increase in peak oxygen pulse (13.4 ± 3 vs. 18.9 ± 16 mL/beat, Δ5.5 ± 15, P = 0.001), peak VO2/kg (19.7 ± 5 to 23.4 ± 13 mL/kg/min [Δ 3.7 ± 10, P = 0.043]), and corresponding MET (5.6 ± 1 to 6.7 ± 4 [Δ1.1 ± 3, P = 0.03]). No improvement was observed in patients with failed procedures. Conclusion Successful ablation improves exercise performance and QoL in asymptomatic LSP‐AF patients.